High impedance arcing fault detection and classification using wavelet transform-neural network technique - Abdulhamid A. Abohagar, 1978-, author; Mohd. Wazir Mustafa, supervisor; Fakulti Kejuruteraan Elektrik (2015)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2015